Portal vein embolization and its effect on tumour progression for colorectal cancer liver metastases. Issue 10 (24th June 2015) - Simoneau, E.; Hassanain, M.; Shaheen, M.; Aljiffry, M.; Molla, N.; Chaudhury, P.; Anil, S.; Khashper, A.; Valenti, D.; Metrakos, P.
<x xml:space="preserve">Abstract</x> Background The aim of this study was to evaluate the long‐term outcomes of patients with colorectal cancer liver metastasis (CRCLM) exhibiting disease progression after portal vein embolization (PVE). Methods Patients with CRCLM requiring PVE before hepatectomy between 2003 and 2014 were included. Clinical variables, and liver and tumour volumes determined by three‐dimensional CT volumetry were assessed before and after PVE. Overall and disease‐free survival data were obtained. Univariable and multivariable logistic regression analyses were performed to identify predictors of tumour progression after PVE. Results Of 141 patients who underwent PVE, 93 (66·0 per cent) had tumour progression and 17 (12·1 per cent) developed new contralateral lesions. Significantly fewer patients had resectable disease in the group with disease progression than among those with stable disease: 43 (46 per cent) of 93 versus 36 (75 per cent) of 48 respectively (P = 0·001). Median survival was similar in patients with and without tumour growth after PVE: 22·5 versus 26·0 months for patients with unresectable tumours (P = 0·706) and 46·2 versus 52·2 months for those with resectable disease (P = 0·953). However, disease‐free survival for patients with tumour progression after PVE was shorter than that for patients with stable disease (6·0 versus 20·2 months; P = 0·045). Response to neoadjuvant chemotherapy was the only significant factor associated with tumour progression in multivariable analysis. Conclusion Tumour progression after PVE did not affect overall survival, but patients with resected tumours who had tumour growth after embolization experienced earlier recurrence. A borderline response to neoadjuvant chemotherapy seemed to be associated with tumour progression after PVE.